Levels of cardiorespiratory fitness in men exerts strong impact on lymphocyte function after mitogen stimulation - Dorneles, Gilson P.; Lira, Fabio Santos [UNESP]; Romão, Pedro R.T.; Kruger, Karsten; Rosa-Neto, Jose Cesar; Peres, Alessandra; Antunes, Barbara Moura [UNESP] (American Physiological Society, 2021)
Relationship between lymphocyte function and cardiorespiratory fitness (CRF) is well-documented at rest; however, upon mitogen stimulation the proliferation and cytokine production alters, but knowledge is incipient about lymphocyte responses after mitogen stimulus according to CRF. So, the purpose of the present study was to analyze the lymphocyte function according to the physical fitness status of healthy young men. The study is divided in two experiments being the first analyzing the lymphocyte phenotypes profile and the inflammatory responses, according to CRF, in lymphocyte cell cultures treated for 48 h with concanavalin A (ConA). The second experiment analyzed the proliferation, reactive oxygen species production, viability, and mitochondrial polarization state in lymphocytes treated with ConA in different concentrations, considering the CRF levels. The results showed a difference in the percentage of total lymphocytes expression between groups (P = 0.011) observing a lower lymphocytes T expression in the group with high maximal oxygen consumption (V_ O2max) when compared with the moderate V_ O2max group. When treated with ConA, the lymphocytes of the low V_ O2max group released higher TNF-a concentration (P = 0.032), reflecting an elevated TNF-a/IL-10 ratio (P = 0.055), parallel with lower IL-6 production (P = 0.027), mainly when compared with the moderate V_ O2max group. In addition, there is a positive relationship between V_ O2max and IL-6 production (r = 0.507; P = 0.016), whereas the percentage of total lymphocytes (LyT%) shows a negative trend with V_ O2max (r = 0.497; P = 0.060). Also, individuals with lower V_ O2max showed reduced absolute and relative ROS production, lower cell proliferation, and higher mitochondrial membrane depolarization. In conclusion, cardiorespiratory fitness degree exerts a strong impact on lymphocyte function after mitogen stimulation. NEW & NOTEWORTHY The innovation of the research is to elucidate the impact of different physical fitness status on metabolism, cell proliferation, and lymphocyte activity and, consequently, on the specific inflammatory response against a mitogen.
Keywords: Immune system; Inflammation; Oxidative stress; Physical fitness status